Collaborative Security Governance Against Transnational Extremism: Policy Lessons From Isis Regional Affiliates - Suhirwan Suhirwan; Siswo Hadi Sumantri; Lukman Yudho Prakoso (Universitas Jenderal Ahmad Yani, 2026)
This study examines the evolution of ISIS regional affiliates and the growing importance of collaborative security governance in addressing transnational extremism in the digital era. Using a qualitative comparative case-study approach, the research draws on semi-structured interviews with fifteen academics, policymakers, governance experts, and security practitioners from various countries, supported by secondary data and reflexive thematic analysis. The findings reveal that ISIS has transformed from a territorially based movement into a decentralized digital network supported by groups such as ISIS-K, ISCAP, and Boko Haram. The use of online propaganda, digital recruitment, and cryptocurrency financing has strengthened cross-border radicalization and extremist resilience. The study also identifies fragmented governance, weak institutional coordination, and limited cyber-governance capacity as major challenges in countering adaptive extremism. This article argues that adaptive governance, intelligence sharing, and multi-stakeholder cooperation are essential for strengthening global resilience against contemporary extremist threats.